2000
DOI: 10.1385/bter:76:3:193
|View full text |Cite
|
Sign up to set email alerts
|

Zinc Status and Immune System Relationship

Abstract: The essentiality of zinc for humans was first documented by Prasad in the 1960s. The main clinical manifestations associated with zinc deficiency are growth retardation, hypogonadism, diarrhea, and increased susceptibility to infectious diseases. Thus, in the past 25 yr, there was an increased interest of researchers in studying the role of zinc in human immunity. Although mechanistic research has been carried out using animal models, there are several studies in humans with similar results. This work is an at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0
5

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(50 citation statements)
references
References 41 publications
1
43
0
5
Order By: Relevance
“…Zn content of the prostate gland, the seminal fluid and ejaculated sperm are very high and testicular Zn is essential for spermatogenesis. Zn deficiency has also been reported to be a cause of hypogonadism [83]. Abbreviation: DMT-1= divalent metal transporter, Fpn1= ferroportin-1, TFR1= transferrin reseptor-1, TFR2= transferrin reseptor-2.…”
Section: Zinc (Zn)mentioning
confidence: 99%
“…Zn content of the prostate gland, the seminal fluid and ejaculated sperm are very high and testicular Zn is essential for spermatogenesis. Zn deficiency has also been reported to be a cause of hypogonadism [83]. Abbreviation: DMT-1= divalent metal transporter, Fpn1= ferroportin-1, TFR1= transferrin reseptor-1, TFR2= transferrin reseptor-2.…”
Section: Zinc (Zn)mentioning
confidence: 99%
“…Zn and Hg also exert a critical influence on the mammalian immune system (Salgueiro et al 2000, Rink & Gabriel 2001.…”
Section: Toxicologymentioning
confidence: 99%
“…Zinc is a trace element involved in numerous enzymatic reactions, biochemical functions, and immune responses (3,4) and is, therefore, required for growth and cellular function. The results from meta-analyses and pooled analyses of multiple highquality worldwide intervention studies have shown that the impairment of zinc absorption alone contributes substantially to growth failure (5).…”
Section: CDmentioning
confidence: 99%